Notes on Etching Heaven: A Fact and Fiction Expedition to the Cosmogony of the Map - Leech, Angus (UnderCurrents: Journal of Critical Environmental Studies, 2001)
The map systems of the Western world have their origins in geometric grids developed to chart the Heavens-the starry abode of divine rationality, and of perfect order.